Corporate Perceptions of the Business Case for Supplier Diversity: How Socially Responsible Purchasing can ‘Pay’ - Worthington, Ian (Journal of business ethics, 2009)
In exploring corporate perceptions of the business case for supplier diversity (SD), this paper reports on a cross-national study of large purchasing organisations (LPOs) that had introduced, or were in the process of introducing, purchasing initiatives aimed at ethnic minority businesses (EMBs). The research investigates how LPOs portray the benefits of this form of socially responsible purchasing and suggests a business case construct based on four component elements. It also highlights a number of contextual factors that appear to have shaped business case rationales. The paper concludes with a discussion of issues of cost and contingent influences affecting SD programmes and points to possible areas for future research.